Deformation of spiritual values in modern society: Causes and consequences - Boybekova Shahnoza Aliyevna (Goodwood Publishing, 2025)
Purpose: This study aims to examine the structural transformation of values in modern society by identifying the main socio-economic, political, and cultural factors that influence their change. It emphasizes how modernization and the complexity of social dynamics reshape collective priorities and individual orientations. Research methodology: The research employs a qualitative descriptive approach supported by content analysis of academic literature, policy documents, and sociological data. Comparative analysis is applied to highlight the interplay between traditional and modern value systems, while contextual interpretation helps to map the drivers of change in contemporary society. Results: Findings indicate that social and economic intensification, political reforms, and the diversification of cultural life have generated a multilayered value system. Values once dominant, such as collectivism and hierarchical conformity, are increasingly replaced or reinterpreted by individual responsibility, innovation, and cultural pluralism. The research also shows that the evolution of values follows a dynamic hierarchy, where some gain centrality while others decline in significance. Conclusions: The study concludes that structural change of values is not random but a response to broader systemic updates. Modern society demonstrates an adaptive capacity, ensuring continuity of ethical frameworks while integrating new norms required by globalization and technological development. Limitations: The research is primarily conceptual and relies on secondary sources; empirical field data from diverse societies are still limited. Contribution: This article contributes to the theoretical understanding of value transformation by linking social change with the evolving hierarchy of values in contemporary life.